2014
DOI: 10.1111/zph.12165
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Usage in Chicken Production in the Mekong Delta of Vietnam

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 20 publications
8
127
0
Order By: Relevance
“…The study indicated a total usage of 690.4 g (Ϯ203.6 g) of antimicrobial compound per chicken produced, which is very high compared with European standards (6).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The study indicated a total usage of 690.4 g (Ϯ203.6 g) of antimicrobial compound per chicken produced, which is very high compared with European standards (6).…”
Section: Discussionmentioning
confidence: 70%
“…Antimicrobials used in animal farming and human medicine are largely similar (4). In Vietnam, extensive use of antimicrobials in farming has been documented, including compounds considered to be critical for human medicine, such as fluoroquinolones, macrolides, and aminoglycosides (5,6). As a result, high levels of antimicrobial resistance (AMR) in zoonotic bacteria, such as nontyphoid Salmonella and Campylobacter spp., have been reported both on farms and in meat products (7)(8)(9).…”
mentioning
confidence: 99%
“…Six publications [15,16,17,18,19,20] reported AMU in terrestrial animal production (pigs and chickens), and two in aquaculture production [21,22]. Except for one publication that investigated antimicrobial use to raise chickens in integrated fish–chicken farms [21] in Thailand, and another one that investigated fish and shrimp farms in both Thailand and Vietnam [22], the remaining publications investigated AMU exclusively in Vietnamese farms.…”
Section: Resultsmentioning
confidence: 99%
“…All studies report types and classes of antimicrobials used on farms over a specified period of time. In three publications (two of which relate to the same study farms), quantitative data are also presented [16,18,23]. In two of these studies [16,18] consumption is presented in terms of grams of antimicrobial compound to produce one kilogram of chicken or pig produced, whereas in the other [23], consumption for chickens was expressed as “treatment incidence” [24].…”
Section: Resultsmentioning
confidence: 99%
“…Most antibiotics used in poultry production in the country are administered prophylactically in drinking water or incorporated in feed (Lawal et al, 2015), as it is the case in Vietnam (Carrique-Mas et al, 2015) and in Uganda (Bashahun and Odoch, 2015). In Nigeria Ogunleye et al (2008) reported that seven of the eight farms studied used between three and seven different antimicrobial agents at different times for prophylaxis or treatment purposes.…”
Section: Table Imentioning
confidence: 99%